(untitled) (Praxis Educativa, 2024)
From a virtue-based approach to digital education, this article aims to analyse the perception of a group of Spanish adolescents and their practice of two civic virtues on the Internet and social media: solidarity and tolerance, crucial for social engagement and for building humanising interpersonal relationships. For this purpose, a quantitative and qualitative research methodology was used. A survey was administered to a purposive sample of 131 high school students. The results were analysed with SPSS.25 and Atlas.ti.8.4. The respondents expressed an abstract positive perception of the possibilities of the Internet for promoting both virtues; however, on a personal level, their practice of these virtues on the web was limited. The collected data suggest the need to strengthen a social understanding of ICTs and accompany this kind of use, steering them towards an engagement that looks into future life plans, in contrast to consumerist and individualist uses.